2019
DOI: 10.1186/s10194-019-1030-z
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of onabotulinumtoxinA treatment for the prevention of headaches in adults with chronic migraine in Australia: a retrospective study

Abstract: BackgroundOnabotulinumtoxinA (BOTOX®, Allergan plc, Dublin, Ireland) is approved for the preventive treatment of headaches in adult patients with chronic migraine (CM) in Australia by the country’s reimbursement mechanism for medicines, the Pharmaceutical Benefits Scheme (PBS). To our knowledge, this study represents the first focused report evaluating real-world evidence of onabotulinumtoxinA treatment via the PBS in Australian clinics.MethodsThis study reviewed the medical records of adults with inadequately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 25 publications
4
27
1
1
Order By: Relevance
“…The phase 3 PREEMPT trials demonstrated that onabotulinumtoxinA significantly reduced the frequency of headaches and migraine days compared with placebo 30–32. Our findings concurred with those from many observational studies that have confirmed the safety and efficacy of onabotulinumtoxinA for the prevention of chronic migraine 16 18–23. The proportion of patients achieving a ‘good response’ (defined as ≥50% reduction in headache days per month) in our study was 88%, which was notably higher than the ‘good response’ rate reported in other real-world evidence studies (74% reported by Stark et al ,23 46% for headache reduction and 74% for migraine reduction reported by Kalil et al 19 and 39.5% at week 24% and 61.1% at week 108 reported by the COMPEL study 18.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The phase 3 PREEMPT trials demonstrated that onabotulinumtoxinA significantly reduced the frequency of headaches and migraine days compared with placebo 30–32. Our findings concurred with those from many observational studies that have confirmed the safety and efficacy of onabotulinumtoxinA for the prevention of chronic migraine 16 18–23. The proportion of patients achieving a ‘good response’ (defined as ≥50% reduction in headache days per month) in our study was 88%, which was notably higher than the ‘good response’ rate reported in other real-world evidence studies (74% reported by Stark et al ,23 46% for headache reduction and 74% for migraine reduction reported by Kalil et al 19 and 39.5% at week 24% and 61.1% at week 108 reported by the COMPEL study 18.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, onabotulinumtoxinA treatment is one of the most successful management approaches for chronic migraine 18–23. Three recent studies found that prophylactic onabotulinumtoxinA treatment for chronic migraine was associated with statistically significant improvements in depression and anxiety symptoms16–18 and that this improvement in comorbid depression and anxiety may be independent of the reduction in headache frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Onabotulinumtoxin A (BT-A) is a safe and effective preventive treatment for CM, as shown in the Phase 3 Research Evaluating Migraine Prophylaxis Therapy (PREEMPT) trials [8][9][10][11][12]. Several real-life studies confirmed its safety and efficacy in clinical practice [13][14][15][16][17][18][19][20][21][22] and showed that a shorter disease duration, some characteristics of headache (ocular, imploding), allodynia, and the absence of medication overuse and depressive symptoms are predictors of clinical response [23][24][25][26][27][28][29][30][31][32][33]. However, it is common experience to observe fluctuations in the clinical response to BT-A as to other preventive treatments.…”
Section: Introductionmentioning
confidence: 97%
“…Onabotulinumtoxin A (BT-A) is a safe and effective preventive treatment for CM, as shown in the Phase 3 Research Evaluating Migraine Prophylaxis Therapy (PREEMPT) trials [7][8][9][10][11]. Several real-life studies confirmed its safety and efficacy in clinical practice [12][13][14][15][16][17][18][19][20][21] and showed that a shorter disease duration, some characteristics of headache (ocular, imploding), allodynia, and the absence of medication overuse and depressive symptoms are predictors of clinical response [22][23][24][25][26][27][28][29][30][31][32]. However, it is common experience to observe fluctuations in the clinical response to BT-A as to other preventive treatments.…”
Section: Introductionmentioning
confidence: 97%